2011
DOI: 10.1007/s11707-011-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical constraints on the depositional environment of Upper Devonian radiolarian cherts from Loei, north-eastern Thailand

Abstract: Late Devonian radiolarian chert sequences in the Indochina block of north-eastern Thailand are exposed in a narrow belt located to the east of Loei province. The analyzed radiolarian cherts were collected from Chiang Klom, Sumnoi and Pha Samyod localities. They are characterized by high silica content ( > 90 wt.%), high aluminum content and low iron content (Al 2 O 3 /(Al 2 O 3 + Fe 2 O 3 ): geomeans 0.91, 0.88 and 0.92). The Al/(Al + Fe + Mn) values are high in both cherts and interbedded shales (geomean 0.89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Plot of NASC‐normalized Ce/Ce* against Eu/Eu* of the Upper Devonian chert/siliceous shale sequences in this study (VR, PS) and those reported from South China (SW, BSI and FSI) (Chen et al ., ), NE Thailand (CK, SN and PSY) (Udchachon et al ., ) and N Thailand (CD) (Hara et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Plot of NASC‐normalized Ce/Ce* against Eu/Eu* of the Upper Devonian chert/siliceous shale sequences in this study (VR, PS) and those reported from South China (SW, BSI and FSI) (Chen et al ., ), NE Thailand (CK, SN and PSY) (Udchachon et al ., ) and N Thailand (CD) (Hara et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The result suggests that most of our samples from Vilabouly show close Ce/Ce* values to those from South China which are interpreted as open–marine conditions. However, they differ in Eu/Eu* values, as South China has high positive Eu anomalies interpreted as hydrothermal and channelled through deep–seated faults (Chen et al ., ), while most of the samples from Ban Phonxai show close Ce/Ce* values to those from N and NE Thailand which are interpreted as oceanic and continental margin environments, respectively (see Hara et al ., ; Udchachon et al ., ). It was suggested that high positive Eu anomaly in cherts and shales from NE Thailand involves weathered feldspar contribution from the contemporaneous volcanisms (Udchachon et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although siliceous rock may have a uniform texture and a relatively simple mineral composition, the geochemical studies of siliceous rocks have been widely applied to determine their origins, depositional environments, palaeogeographical variations, palaeo‐upwelling zones, primary productivity areas, and sediment provenance indicators (Chen, Qing, Yan, & Li, ; Eker, Sipahi, & Kaygusuz, ; Garbán et al, ; Halamić, Marchig, & Goričan, ; Igor & Kemkina, 2015; Kato, Nakao, & Isozaki, ; Murray, ; Muttoni & Kent, ; Owen, Armstrong, & Floyd, ; Ragueneau et al, ; Ran et al, ; Udchachon, Thassanapak, Feng, & Chonglakmani, ; Yu, Dong, Widom, Chen, & Lin, ). At present, there are many theories about the formation mechanism of the Wufeng siliceous rock.…”
Section: Introductionmentioning
confidence: 99%
“…The first simulations were initially studied for understanding the chemical reactions in aquatic environments in order to solve water pollution hazards. These simulations also assessed the diagenetic processes such as natural formation and alteration of rocks (Lai et al, 2018;Limarino et al, 2017;Crémière et al, 2016;Klunk et al, 2015;Udchachon et al, 2011). It is impossible to reproduce the exact behavior of most geochemical systems in the laboratory due to the complexity and diversity in time scale of the reactions in geological environments (Klunk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%